Pelatihan Produksi dan Pemasaran Produk Nugget Nabati untuk Membentuk Wirausaha Baru di Bonto Langkasa Kabupaten Pangkep - Awaluddin, Sri Prilmayanti; Abdullah, Abdullah; Azis, Indrawan; Nurani, Nurani; Muntasir, Muntasir (Jurnal Pengabdian UNDIKMA, 2022)
This community service aims to train teenagers and homemakers to improve their skills in producing and marketing plant-based nuggets to form young entrepreneurs in the Bonto Langkasa sub-district, Pangkep district. This service method was carried out through stages 1) Pre-implementation of activities, including analysis of partner situations, obtaining permits, and providing facilities and services for service activities; 2) The implementation of the extension includes the delivery of materials, two-way discussions, and production practices by the participants. 3) Evaluation of activities. Thirty participants attended this activity until the activity ended. The results of this service activity showed that 100 percent were happy and enthusiastic about this service activity. This activity can provide knowledge about simple bookkeeping, marketing, and producing processed organic vegetable nuggets to form new entrepreneurs. The existence of community groups in Bonto Langkasa Village, Pangkep Regency, especially young women and housewives who can process and produce organic vegetable nuggets, can improve family nutrition and increase people's income if marketed. The contribution of this service is organic vegetable nuggets that are of high quality, clean, and safe for consumption and marketing.